Addressing the Needs of an Aging Population in the Health System: The Australian Case. Issue 3 (3rd July 2017) - McPake, Barbara; Mahal, Ajay
Abstract: Although smaller as a proportion of total population than Western Europe or Japan, almost 15% of Australia's population is aged 65 years and over and expected to increase to nearly 22.5% by 2050. Health policy makers in Australia have tried multiple approaches to address the growing health care needs of an aging population and the related burden of noncommunicable conditions (NCDs). We assess how these interventions—in primary care, hospital services and private health insurance—have influenced outcomes and draw inferences from their successes and some of their main difficulties. Among the key lessons from the Australian experience, also relevant for the Asia Pacific region, are the challenge of aligning financial incentives in a mixed public-private health care and financing system and the difficulty of reforming a medically-centered primary care model to one that integrates care across a range of dimensions, including the services of allied health professionals and long-term care services. The clearest specific policy lessons for the region include the suggestions that public subsidy of private health insurance is unlikely to be an efficient approach to reducing the health-related cost burdens of aging populations, and that countries should build alternatives to fee-for-service payment mechanisms into their plans for achieving Universal Health Coverage. Australians might look to the experience of other countries in the region for additional models of coordination between national government and sub-national divisions and for approaches to reducing the disadvantages faced by minority groups in the health system.